MicroRNA-30a suppresses autophagy-mediated anoikis resistance and metastasis in hepatocellular carcinoma. (1st January 2018) - Fu, Xiu-Tao; Shi, Ying-Hong; Zhou, Jian; Peng, Yuan-Fei; Liu, Wei-Ren; Shi, Guo-Ming; Gao, Qiang; Wang, Xiao-Ying; Song, Kang; Fan, Jia; Ding, Zhen-Bin
Abstract: MiRNA-30a (miR-30a) was previously reported as one of metastatic hepatocellular carcinoma (HCC)-related microRNAs. However, the function of miR-30a on enhancing our biological understanding of HCC metastasis is not clear. This study demonstrated that miR-30a was significantly down-regulated in HCC tissues and cell lines, and was associated with vascular invasion, metastasis potential and recurrent disease in HCC. Functional studies confirmed that miR-30a could inhibit the metastasis of HCC in a well-established nude mouse model of lung metastasis. Moreover, miR-30a was proved to prevent anoikis inhibition of HCC cells in vivo and in vitro. Mechanically, autophagy related protein Beclin 1 and Atg5 were direct downstream targets of miR-30a, and mediated autophagy activity influence of miR-30a in HCC. Taken together, downregulated miR-30a in metastatic HCC mediates Beclin 1 and Atg5-dependent autophagy, which confers anoikis resistance in HCC cells. The molecular basis of autophagy action during this process partly contributes to the HCC metastasis, suggesting that targeting autophagy via miR-30a may have therapeutic implications for the prevention of HCC recurrence/metastasis. Highlights: miR-30a expression is correlated with metastasis in HCC. miR-30a inhibits the metastasis of HCC in vivo. miR-30a prevents anoikis inhibition of HCC cells in vivo and in vitro. Downregulated miR-30a in metastatic HCC mediates Beclin 1 and Atg5-dependent autophagy.